Adult Education for China‟s “Floating Population”:A Conceptual Framework to Guide Policy, Practice and Research - Yibing Liu; Thomas Valentine (Adult Education Research Conference, 2012)
Since the 1980s, the demand for workers in the China‘s industrial cities, coupled with the extreme poverty of rural villages, has resulted in a massive migrant population comprised of adult workers from the countryside who move to industrial cities seeking work while maintaining strong ties to the villages in which they have permanent residence permits. Approximately 200 million Nong-ming-gong (rural migrant workers) now constitute the largest mass migration in human history. These migrant workers have provided China with an indispensable resource for city construction and economic prosperity. However, the cost to the migrant workers themselves has been extreme, as geographic relocation results in widespread psychological and social dislocation.